Influencia de la asertividad comunicacional en la educación en línea con estudiantes de sexto semestre de la Carrera de Comunicación Social de la UTB-eq, año 2021 - Barzola Rizo, Paulina Xiomara (2021)
The question that arises about the influence that communicational assertiveness can have within online education creates new questions that open the way to this research, knowing the importance of assertiveness within intrapersonal relationships is essential for good development and academic training of students in the sixth semester of the Social Communication career at the Technical University of Babahoyo Quevedo extension. Contrasting the experiences of students within face-to-face and virtual education will be useful to expose the need of human beings to interact with others and generate communication links, these will be analyzed and interesting points are reached that potentially contribute to the collection of information both empirical and bibliographic.